1997
DOI: 10.1086/304654
|View full text |Cite
|
Sign up to set email alerts
|

Dust in Starburst Galaxies

Abstract: To investigate the nature of starbursts' dust, we constructed a model of the stars and dust in starburst galaxies and applied it to 30 observed starburst spectral energy distributions (SEDs). The starburst model was constructed by combining two stellar evolutionary synthesis models with a model describing the radiative transfer of stellar photons through dust. The stellar evolutionary synthesis models were used to compute the dust-free SEDs for stellar populations with ages between 1x10^6 and 15x10^9 years. Us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
316
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(355 citation statements)
references
References 54 publications
29
316
2
Order By: Relevance
“…However, we also For comparison, the Calzetti law is also indicated by a dotted green line. It has been shown that the Calzetti law is the result of the attenuation by a medium with an SMC-type dust (Gordon et al 1997;Inoue 2005). We can recover this result using Eq.…”
Section: Attenuation Curvessupporting
confidence: 53%
“…However, we also For comparison, the Calzetti law is also indicated by a dotted green line. It has been shown that the Calzetti law is the result of the attenuation by a medium with an SMC-type dust (Gordon et al 1997;Inoue 2005). We can recover this result using Eq.…”
Section: Attenuation Curvessupporting
confidence: 53%
“…This clumpy geometry is also chosen since it has been shown to reproduce both the observable continuum properties of starburst galaxies and the Calzetti attenuation law (Gordon et al 1997;Witt & Gordon 2000;Vijh et al 2003). Finally, this also allows us to make a detailed investigation into the continuity of the extensive grid of radiation transfer models by Schaerer et al (2011).…”
Section: D Geometries Model Parameters and Model Outputmentioning
confidence: 99%
“…We consider these possibilities in Paper II. Mathis et al 1977 andWhite 1979. b Values from Gordon et al 1997.…”
Section: Ultraviolet Faintnessmentioning
confidence: 99%
“…Finally, the scattering geometry is constrained by a wealth of observations. Interstellar polarization and reddening (e.g., Breger 1986Breger , 1987, atomic and molecular line absorption (Federman 1982;Bohlin et al 1983;White 1984;White et al 2001), radio line emission (Gordon & Arny 1984;Federman & Wilson 1984;Bally & White 1986), and far-infrared (FIR) thermal emission (Castelaz, Sellgren, & Werner 1987;White & Bally 1993) indicate a low level of interstellar matter across most of the cluster but more on the western side, perhaps with some optically thick dust southwest of the star 23 Tau (Merope). Enough material is probably in front of the major stars to dominate the scattered light budget for forward-scattering grains, but some of the densest gas and dust may lie behind or among the stars on the west side of the cluster.…”
Section: Introductionmentioning
confidence: 99%